MultiPluriTrans in Educational Ethnography Approaching the Multimodality, Plurality and Translocality of Educational Realities - Bollig, Sabine; Neumann, Sascha; Honig, Michael-Sebastian (Pädagogik, 2015)
Ethnography has established itself as a key strategy of qualitative research in education, because it is so versatile, flexible, and ambiguous. Its growing importance coincides with an increasing diversity of »discovered« educational realities. In the process, many basic assumptions have turned into genuine tasks of research. Where are the places and times of learning, education, and social work to be found? Who are the actors and addressees? How are education and learning performed and enacted?The contributions to this volume discuss the multiple challenges that ethnographic research has to confront when exploring the multimodality, plurality, and translocality of educational realities